Congenital segmental lichen sclerosus et atrophicus. - Bonifazi, E. (European Journal of Pediatric Dermatology, 2020)
In the literature there are about ten cases of lichen sclerosus (LS) distributed along the lines of Blaschko or in any case segmental, but none is congenital or diagnosed in the child. LS is considered an autoimmune disease, both because it is frequently associated with other autoimmune disorders and because autoantibodies against extracellular matrix protein 1 have been demonstrated (2). Like many other autoimmune diseases – psoriasis, lupus erythematosus, scleroderma, vitiligo etc. – even LS, although not frequently, can be distributed unilaterally according to Blaschko’s lines; cases of vitiligo on one segment and lichen sclerosus on another segment of the same patient have also been described (1). This distribution is expression of a mosaicism due to a post-zygotic mutation. As regards topical treatment, though LS responds well to corticosteroids, we prefer tacrolimus to not accentuate its atrophic tendency.